Strengthening Teachers’ Pedagogical Competence through Theasys-Based Learning Media Training: A Community Service Program at MAN 1 Sleman: Pelatihan Media Pembelajaran Berbasis Theasys untuk Penguatan Kompetensi Pedagogik Guru MAN 1 Sleman - Nanang Khuzaini; Naela Faza Fariha; Nuryadi Nuryadi; Nafida Hetty Marhaeni; Muhammad Irfan Rumasoreng; Arie Purwanto (Room of Civil Society Development, 2026)
This community service program aimed to improve the pedagogical competence of MAN 1 Sleman teachers through training in developing Theasys-based learning media. The program involved 45 teachers and was implemented through active participation, activity-oriented, program-based, and independent learning approaches. The evaluation instrument was a questionnaire consisting of 20 items distributed across five indicators: understanding of learning media, understanding of software, understanding of Theasys features, ability to create Theasys-based learning media, and ability to integrate the media into classroom learning. The data were analyzed using descriptive quantitative analysis by comparing participants’ understanding before and after the training. The results showed that the average level of participants’ understanding increased from 2.4% before the training to 90.4% after the training. The highest improvement was found in the ability to create Theasys-based learning media, which increased from 2% to 98%. In addition, 92% of participants stated that the training was highly beneficial for developing learning media, and the attendance rate of ≥85% indicated active participation throughout the program. These findings suggest that Theasys-based training can support teachers in developing interactive visual learning media according to subject-specific needs.